Natural occurrence and biosynthesis of auxins in chloroplast and mitochondrial fractions from sunflower leaves - Fregeau, J.A.; Wightman, F.
Endogeneous levels of 3-indolylacetic acid (IAA)and phenylacetic acid (PAA)have been determined in purified chloroplast and mitochondrial fractions from sunflower leaves by employing modern chromatographic methods of analysis. The capacity of each organelle fraction to synthesize IAA and PAA when supplied with l-tryptophan or l-phenylalanine has also been investigated. Intact chloroplast were isolated from young leaves by rapid homogenization followed by a Percoll centrifugation procedure; mitochondria were isolated by a similar method involving centrifugation through a Percoll step gradient. Gas chromatographic analysis (GLC)of purified fractions from chloroplast and mitochondrial ether extracts revealed the presence of both IAA and PAA as endogenous substances in each organelle. The levels of each auxin appear to be much higher in chloroplasts than in mitochondria. Both organelle fractions were shown to produce IAA or PAA when supplied with the appropriate precursor amino acid, the amount of each auxin synthesized per mg protein being greater in the mitochondrial than in the chloroplast reaction system. The isolation of each auxin product was achieved by high performance liquid chromatography (HPLC)followed by GLC analysis of fractions derivatized by methylation or pentafluorobenzylation. Identification was obtained by cochromatography with the authentic compound and by gas chromatography-mass spectrometry (GC-MS).
Keywords: AUXINS; BIOSYNTHESIS; CHLOROPLASTS MITOCHONDRIA; ENDOGENEOUS AMOUNTS; SUNFLOWER